Isolated Epitrochlear Filarial Lymphadenopathy: Cytomorphological Diagnosis of an Unusual Presentation - Priya SAHU; Prajwala GUPTA; Minakshi BHARDWAJ; CK DURGA (Federation of Turkish Pathology Societies, 2020)
Filariasis is a major public health problem in tropical countries like India. Despite the large number of people at risk, detection of eggs with or without larva (microfilaria) on fine-needle aspiration cytology is very unusual, especially in an uncommon site or incidentally detected in clinically unsuspected cases of filariasis with the absence of microfilariae in the peripheral blood. A 19-year-old male presented with swelling over medial aspect of left arm (just above the elbow), with no other specific signs and symptoms. Fine needle aspiration cytology revealed an adult gravid female filarial worm in a background of reactive lymphoid cells and lymphohistiocytic clusters. We report a case with elaborate fine needle aspiration cytology findings of filarial worm infestation with unusual presentation of isolated epitrochlear lymph node involvement in a clinically unsuspected case and recommend clinicians and pathologists to consider a high index of suspicion for such infections at uncommon sites especially in endemic territories, as early diagnosis and treatment prevent the more severe manifestations of disease.